Gender dynamics within food systems in displacement contexts: Experiences from displaced populations in Nampula, Mozambique - Synnestvedt, Thea; Maviza, Gracsious; Maphosa, Mandlenkosi (Frontiers Media, 2025)
In Nampula province, Mozambique, internally displaced and refugee communities live in settlements situated at the outskirts of Nampula city. This paper explores the intersection of gender and food systems in displacement contexts by focusing on the experiences of displaced populations and examining how displacement exacerbates existing gender inequalities and shapes access to food resources and livelihoods. It delves deeper into the barriers and opportunities men and women face in orienting themselves within food systems in displacement contexts. A participatory rural appraisal methodology, disaggregated by gender, was implemented in displaced communities in Nampula. The gendered analysis found that displacement dynamics affected food systems, where gender dynamics play a central role in determining resilience capacities. The findings of this study contribute to the scholarship on the nexus between climate security, food security and gender, bringing internally displaced and refugee communities into the fore of food system discussions.